Obesidad materna como factor de riesgo de hemorragia post parto por atonía uterina, Hospital Regional Docente de Trujillo, período 2004 - 2013 - Vasquez Calderon, Anthony Renzo (2016)
To determine whether maternal obesity is a risk factor for postpartum hemorrhage uterine inertia, at Regional Hospital of Trujillo, in the period 2004-2013. Method: An analytical study of retrospective case-control with the medical histories of first time pregnant women who were treated by vaginal delivery at Regional Hospital of Trujillo in the period 2004-2013 were not carried out. Of these those that presented diagnosis of postpartum hemorrhage uterine inertia, in addition to meeting the inclusion and exclusion criteria were selected. A total of 47 cases and a total of 94 controls were obtained. In each group the dependent variable was determined by body mass index (BMI) to identify maternal obesity. Results: Evidence up to 32% of pregnant women with obesity within cases. The frequency of postpartum hemorrhage due to uterine atony is 33%. Maternal obesity is a risk factor for postpartum hemorrhage evidenced by an odds ratio of 4.42 (CI: 95%, p <0.05). You can’t statistically prove a relationship between the degree of obesity and postpartum hemorrhage uterine inertia (p> 0.05). Conclusions: Maternal obesity is a risk factor for postpartum hemorrhage due to uterine atony